(untitled) (Филолошки студии, 2019)
By asking the question of originality in translation i.e. authorship in translation, the article defines translation as the other original of which the translator is the author. The translation as the other original emerges from the original culture, breaks its ties with it and adds to its characteristic by adopting linguistic, literary and cultural features of the translation culture. In this way the translation stops being the fact of the original culture just as it never completely succeeds to become the fact of the translation culture. The translation thus exists in the space of affiliated nonaffiliation, it starts a dialogue i.e. polilogue between the original and translation culture and becomes a fact of both cultures, which through translation get into contact, communicate and influence each other.